G×E Interaction Analysis by Ammi Model for Fodder Yield of Dual Purpose Barley Genotypes - Verma, Ajay; Kumar, V.; Kharab, A. S.; Singh, GP (International Journal of Bio-resource and Stress Management, 2020)
Numerous statistical methods have been proposed to estimate the yield behavior of genotypes to diverse environmental conditions. Large number of research studies has shown a significant effect of environmental as well as of G×E interaction yield of genotypes. G×E interaction has been analyzed by the additive main effects and multiplicative interaction model as this combines the analysis of variance for the genotype and environmental main effects and the principal component analysis with multiplicative indices.Combined AAMI analysis of variance, for 16 dual purpose barley genotypes evaluated across 08 environments of the country, showed significant differences for genotypes, environments and their interactions. Most of type 1 measures selected (EV1, AMGE1, SIPC1 and D1), genotypes G5, G6, G8 and G10; while type 2 favoured (EV2, AMGE2, SIPC2, D1 and ASV), genotypes G11 G14 G10 and G9; due to type 3 of AMMI parameters (EV4, AMGE4, SIPC4 and D4), genotypes G13, G14, G7 and G8; according to the type 5 measures accounted for maximum G×E interaction signal pointed towards ( EV5, AMGE5, SIPC5 and D5) G13, G14, G8 and G16 desirable genotypes. Hierarchical clustering of AMMI based measures along with yield could be clustered with four distant groups. Group I contains AMGE3, AMGE5, IPCA2, IPCA3, IPCA4 and average yield. Group II contains only SIPC1, SIPC2 SIPC3 SIPC5 measures. Group III contains EV2, EV3, with IPCA5 and IPCA6. Largest group IV joined D1, D2, D3, D5, ASV, ASTAB1, ASTAB2 and ASTB5.